Water reuse in the Middle East and North Africa: a sourcebook - Mateo-Sagasta, Javier; Al-Hamdi, M.; AbuZeid, K. (International Water Management Institute, 2022)
Water scarcity in the Middle East and North Africa is intensifying due to rapid population growth, urbanization, and climate change, with average per capita water availability far below global thresholds. Although municipal wastewater offers a growing and renewable source, over half of the 21.5 billion m³ produced annually is lost through discharge or evaporation, while only around 10% is directly reused. Efforts to recover this resource have led to over 400 reuse projects across agriculture, landscaping, and industry, particularly in countries with advanced infrastructure. Treated wastewater supports irrigation and nutrient recovery, with potential for energy generation through methane capture. However, major barriers persist: weak regulatory enforcement, limited cost recovery, and low public acceptance, especially where informal or unsafe reuse occurs. Salinity, pathogens, and emerging pollutants remain challenges for agricultural application, especially without robust treatment or risk mitigation. Improving safety and scale requires better regulation, decentralized systems, inclusive planning, and financial incentives. Integrated reuse strategies linking water, food, and energy systems offer a path to increased resilience, environmental protection, and progress toward sustainability goals.